2023
DOI: 10.3390/toxics11030234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mixed-Phase TiO2–ZrO2 Nanocomposite for Photocatalytic Wastewater Treatment

Abstract: The use of TiO2 nanoparticles for photocatalysis for the degradation of organic dyes under UV light for wastewater treatment has been widely studied. However, the photocatalytic characteristics of TiO2 nanoparticles are inadequate due to their UV light response and higher band gap. In this work, three nanoparticles were synthesized: (i) TiO2 nanoparticle was synthesized by a sol-gel process. (ii) ZrO2 was prepared using a solution combustion process and (iii) mixed-phase TiO2–ZrO2 nanoparticles were synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…According to the Mg high-resolution spectrum analysis, the peak for MgCO 3 was observed at 1305 eV [45]. Regarding the alloying elements, the TiO 2 doublet was observed, with peaks at 458.5 eV and 464.1 eV [45,46,59,61,62], the Nb 2 O 5 peaks of the 3d, 3d 5/2 , and 3d 3/2 doublets were observed at 207.1 eV and 209.8 eV [46], and no peaks of Mo were detected. In addition to the low concentration of Mo in the substrate alloy, its property as a valve metal makes its oxidation less energetically favorable by the MAO method [41,63].…”
Section: Resultsmentioning
confidence: 99%
“…According to the Mg high-resolution spectrum analysis, the peak for MgCO 3 was observed at 1305 eV [45]. Regarding the alloying elements, the TiO 2 doublet was observed, with peaks at 458.5 eV and 464.1 eV [45,46,59,61,62], the Nb 2 O 5 peaks of the 3d, 3d 5/2 , and 3d 3/2 doublets were observed at 207.1 eV and 209.8 eV [46], and no peaks of Mo were detected. In addition to the low concentration of Mo in the substrate alloy, its property as a valve metal makes its oxidation less energetically favorable by the MAO method [41,63].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows the high-resolution XPS spectra of the alloying elements incorporated into the coating. Regarding the alloying elements, doublets related to TiO 2 ( Figure 7 a) and Nb 2 O 5 ( Figure 7 b) were observed at 458.5 and 464.1 eV [ 38 , 44 , 55 , 56 , 57 ] and 207.1 e 209.8 eV [ 44 ], respectively. Mo is present in low quantities in the alloy (5% by weight) and is also known as a valve metal.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the Ti peaks deconvolution, the doublet relative to TiO 2 was observed, with a peak (2p 3/2 ) at 458.5 eV [53]. The Nb spectrum showed the Nb 2 O 5 peaks of the 3d, 3d 5/2 , and 3d 3/2 doublets at 207.1 eV [47].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Kuroda et al [13] studied the effect of thermal treatments on MAO coatings and observed that, even at high temperatures (800 °C), the coating remained amorphous. Upon the Ti peaks deconvolution, the doublet relative to TiO2 was observed, with a peak (2p3/2) at 458.5 eV [53]. The Nb spectrum showed the Nb2O5 peaks of the 3d, 3d5/2, and 3d3/2 doublets at 207.1 eV [47].…”
Section: Structural Characterizationmentioning
confidence: 99%